Effects of applying a graphene/polyurethane composite thermally conductive film on capacitor heat dissipation performance - Qinghua Miao; Ruihan Guo; Pengfei Liu; Jie Li (AIP Advances)
In this study, the effects of applying graphene/polyurethane composite thermally conductive films on heat dissipation performance of capacitors were investigated. By adding graphene as a thermally conductive filler, the thermal conductivity of the composite film could be adjusted by controlling the type and content of the film. Graphene/polyurethane nanocomposite films with different mass fractions were prepared by adding 0.03, 0.06, and 0.3 wt. % graphene. The lattice and valence bond structures of the C atoms in the composite films were analyzed using x-ray diffraction, Raman spectroscopy, x-ray photoelectron spectroscopy, and Fourier transform infrared spectroscopy to investigate the extent of graphene defects and types of functional groups in the composite film materials. The thermal conductivity of the composite films was measured using a heat conduction analyzer, and the thermal diffusion coefficient was calculated. The steady-state thermal analysis showed that the capacitor with the composite film exhibited better thermal performance under the same conditions and significantly reduced the center temperature compared with those observed with other configurations. This study reveals the working mechanism of polyurethane/graphene composite thermal conductive film in the heat dissipation performance of capacitors. This study is of great significance for optimizing the design of capacitors, improving their efficiency, and maintaining long-term stable operation. By improving the thermal conductivity of composite films, capacitors with more uniform overall temperature distributions and reduced surface temperatures can be achieved, which will help improve the overall performance of capacitors and extend their service lives.